THE BURIAL PRACTICES OF THE GRAVETTIAN AND THE EPI-GRAVETTIAN PERIODS IN ITALY, CZECH REPUBLIC, AND RUSSIA - Johan Arif (Jurnal Sosioteknologi, 2021)
This paper describes the burial practice in the Gravettian (early Upper Paleolithic) and the Epi-Gravettian periods (late Upper Paleolithic) in Italy, and the Gravettian period (early Upper Paleolithic) in Czech and Russia. In Italy, the Gravettian and the Epi-Gravettian burial sites were mostly situated in caves because geologically Italy has extensive karstic systems throughout Alpine mountains. Meanwhile, the Gravettian single and multiple burial sites in Czech and Russia were found in an alluvial plain. The single burials are more numerous in the Epi-Gravettian than the Gravettian periods in Italy. Furthermore, Italy has the largest number of the Gravettian single and multiple burials compared to Czech and Russia. If the compass direction and the corpse placement (prosthesis) in the ground and the position of the head are considered, it apparently links to their origin. The ancestors of the Gravettian peoples in Italy, Czech, and Russia are supposed to have originated from the East or Southeast. The disparity of cultural behavior between the Gravettian and the Epi-Gravettian periods in Italy can be deduced by the number of single burial and the environmental condition where the Gravettian period developed during the last glacial maximum (LGM), while the Epi-Gravettian happened in warmer condition.